The relationship between narcissism and the source of control with the job success of the staff of the Azad University, Tehran Central Branch - Mehran Shoorj (Institute of Management fekrenoandish, 2020)
staff job success is a function of their behavioral and personality factors. The aim of this study was to determine the relationship between narcissism and control source with the job success of the staff of the Azad University, Tehran Central Branch. The applied research method was correlational. The statistical population of this study was the staff of Azad University, Tehran Central Branch, which were selected using the available sampling method, and 274 people were selected as the sample, based on Karajsi and Morgan table (1970). Narcissism Questionnaire of Raskin and Terry's (1988), Rutter's control source (1966), and career success of Grbner et al. (2007) were used to gather information. The results of linear regression analysis showed that there is a relationship between narcissism and control source (internal and external) with job success of the staff of Azad University, Tehran Central Branch. Therefore, continuous psychological assessments of narcissistic employees in the workplace can be identified, and career success can be increased by improving the internal control of employees.